A Novel Environmental Route to Ambient Pressure Dried Thermal Insulating Silica Aerogel via Recycled Coal Gangue - Pinghua Zhu; Meng Zheng; Shanyu Zhao; Junyong Wu; Haixun Xu (Advances in Materials Science and Engineering)
Coal gangue, one of the main hazardous emissions of purifying coal from coalmine industry, is rich in silica and alumina. However, the recycling of the waste is normally restricted by less efficient techniques and low attractive output; the utilization of such waste is still staying lower than 15%. In this work, the silica aerogel materials were synthesized by using a precursor extracted from recycled silicon-rich coal gangue, followed by a single-step surface silylation and ambient pressure drying. A low density (~0.19 g/cm3) nanostructured aerogel with a 3D open porous microstructure and high surface area (~690 m2/g) was synthesized, which presents a superior thermal insulation performance (~26.5 mW·m−1·K−1 of a plane packed of 4-5 mm granules which was confirmed by transient hot-wire method). This study offers a new facile route to the synthesis of insulating aerogel material by recycling solid waste coal gangue and presents a potential cost reduction of industrial production of silica aerogels.